2012
DOI: 10.1177/1756287212465457
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic spray cryotherapy for genitourinary malignancies: safety and efficacy in a porcine model

Abstract: ESC in a porcine urothelial treatment model results in full-thickness tissue necrosis in bladder, ureter, and renal pelvis at a minimal treatment settings of 5 s/cycle for six cycles. Adiabatic gas expansion may result in fatal pyelovenous gas embolism and collateral organ injury, as seen in both animals receiving treatment to the renal pelvis in this study. These results raise safety concerns for use of ESC as a treatment modality in urothelial tissues with current device settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…As mentioned above, cryotherapy has already been included in the treatment of urothelial tumor, mainly for bladder tumor so far. [5][6][7][8][9] Compared with the bladder wall, the ureteral wall is relatively thinner. The feasibility and safety of cryoablation of ureter as a potential therapy for urothelial carcinoma remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, cryotherapy has already been included in the treatment of urothelial tumor, mainly for bladder tumor so far. [5][6][7][8][9] Compared with the bladder wall, the ureteral wall is relatively thinner. The feasibility and safety of cryoablation of ureter as a potential therapy for urothelial carcinoma remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Cryoablation offers the potential advantage of treating full-thickness urinary tract wall through ice ball 5 Several previous studies have validated the safety and efficacy of applying cryotherapy in bladder or for bladder tumor through percutaneous or transurethral approach. [6][7][8][9] Based on our prior study on transurethral cryoablation for bladder urothelial carcinoma, our team designed a novel cryoprobe which was applicable through the working channel of a regular ureteroscope (Fr-8/9.8). We conducted an animal study to investigate the safety of ureteral cryoablation in a porcine model and reported the preliminary experience of cryotherapy for patients with UTUC of a solitary kidney.…”
mentioning
confidence: 99%
“…Previous investigations into the use of cryotherapy for the treatment of BCs have primarily employed either argon-JT, percutaneous needles inserted through the abdomen or perineum (36)(37)(38)(39)(40), or transurethral cryogen sprays (41). While both approaches have shown promise, both have potential drawbacks and are limited in the types and stages of BCs they can treat.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous needles are limited to more advanced, muscle invasive cancers (stages 2-4) and the long freeze times (6, 8, or 10 min dual freezes) and tissue penetration may increase operation costs and the likelihood of infections or other unintended injuries. Cryogen sprays are limited to non-invasive and non-muscle invasive cancers (stages 0-1) and the adiabatic gas expansion may result in fatal pyelovenous gas embolisms and collateral organ injury [41]. Although further investigations are needed into the performance of the FrostBite-BC cryocatheter, the results of the pilot in vivo study presented here demonstrated a strong correlation between freeze duration and depth of tissue destruction, with short (15 sec) freezes confining the ablative volume to the sub-mucosa (early stage BCs) and longer (≥30 sec) freezes ablating the full thickness of the bladder wall (late stage BCs).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation